Multilayer validation system for the automation of data in a WSN network with IOT devices - Paz Fernandez, Luisa; Ruiz Rosero, Juan Pablo (Ingeniería Solidaria, 2021)
Introduction: Article resulting from the research "Multilevel validation system with an emphasis on data transmission in a Gateway for the IoT," supported by the Research Line in Internet Applications of the University of Cauca during 2020. Problem: Bridges between wireless sensor networks (WSN) and the Internet are necessary for the for the operation of IoT devices. However, these networks are made up of weak links that can generate packet loss. Objective: present an alternative to improve the data transmission validation process given a frame implemented in a previously developed WSN-IoT system. Methodology: Scientometric review in the WoS and Scopus databases on concepts related to Industry 4.0 (data from 2015 to 2019), IoT and WSN (data from 1990 to 2019), and algorithm generation based on Scrum and test-based development (TDD). Results: A validation application that captures, analyzes frames, and compares the values of the monitored variables in each layer of the implemented model, and ultimately reports the errors detected in the data transmission. Conclusion: with the completion of this investigation, the data transmission validation process of the WSN-IoT system was improved, focused on logistics and monitoring, automating the process. Originality: An alternative to validate the correct transmission of data in a WSN-IoT system is achieved through this research and shown for the first time on trending topics such as industry 4.0, the industrial Internet of things, the supply chain, logistics, and traceability. Limitations: little research in the area of validation, few and delicate hardware devices, in addition to a high dependence on networks to monitor the performance of the designed application.